Padang Panjang Community Reading Park toward UNESCO version of literacy city - Afrina, Cut; Wahyuni, Sri; Dito, Ronal; Utari, Khofifah (Jurnal Kajian Informasi dan Perpustakaan, 2023)
Padang Panjang City Community Reading Park has role developing community literacy skills. Activity in community reading park and efforts to strengthen community literacy to realize the UNESCO version of the Literacy City. The purpose this research to know the role Padang Panjang Community Reading Park to developing community literacy skills and and efforts to strengthen community literacy to realize the UNESCO version of the Literacy City. The research method used the descriptive qualitative. Eight informants from Rimba Bulan, Anggrek Bulan Garbage Bank, Red Orchid, and Makrame Community Reading Park. The study results showed that TBMs were actively developing community literacy skills by training children to read and write and for mothers to do handicrafts such as knitting, and processing plastic waste. The study concludes that TBMs in Padang Panjang City play a significant role in developing community literacy skills and contributing to the realization of the UNESCO version of the Literacy City. TBMs are active, involved in training children in reading and writing and empowering women through craft workshops and plastic waste processing. The TBMs focus on promoting social inclusion and increasing social inclusion literacy. Conclusion this research is community reading park through the diverse programs and collaboration to enhance creativity and service for the community.